IMPACT OF KNOWLEDGE ABOUT MAJOR NON-COMMUNICABLE DISEASES ON LIFESTYLE OF MBBS STUDENTS IN A MEDICAL COLLEGE OF BHUBANESWAR, ODISHA - SUMITRA PATTANAIK; LIPILEKHA PATNAIK; KALYAN KUMAR PAUL; TRILOCHAN SAHU (International Journal of Pharma and Bio Sciences, 2016)
The two major contributors of Non Communicable Disease deaths were cardiovascular diseases (47.9%) and carcinoma (21%). The study aims to evaluate the impact of knowledge of risk factors of major noncommunicable diseases on lifestyle patterns of MBBS students. A cross-sectional study was conducted among the first and final year medical students during the period June & July, 2014. Total 170 students participated in the study of which 91 (53.5%) belonged to first year and 79 (46.5%) final year. The mean knowledge scores were significantly different between first year (mean=11.6 ± 3.2) and final year (mean=16.4 ± 3.7) students (P < 0.001). Smoking (11% vs 1%; p<0.05) and alcohol consumption (14% vs 3%; p<0.001) were significantly higher among final year students. Though final year students have better knowledge, it was not reflected in their lifestyle practices. So interventions should be targeted to bring behaviour changes for adopting a healthy lifestyle.